2021
DOI: 10.1016/j.mechmat.2020.103674
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of size, inertia and porosity on the indentation response of ductile materials

Abstract: Herein, we present a self-similar cavity expansion model that follows from the work of Cohen and Durban (2013b) to analyze the dynamic indentation response of elasto-plastic porous materials while accounting for the plastic strain gradient induced size effect. The incorporation of the plastic strain gradient induced size effect in the dynamic cavity expansion model for elasto-plastic porous materials is the key novelty of our model. The predictions of the cavity expansion model for the material hardness, for d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…see Aboulkhair et al [1] and Heidari et al [25]), so that the range of void volume fractions investigated in this work can be representative of actual metallic materials. Moreover, the range of values investigated for the dimensionless length scale parameter 0 ≤ l /a ≤ 0.002 is similar to that considered by dos Santos et al [41]. The critical dimensionless velocity increases with the normalized length scale, bringing out that size effects hinder the emergence of plastic shocks.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…see Aboulkhair et al [1] and Heidari et al [25]), so that the range of void volume fractions investigated in this work can be representative of actual metallic materials. Moreover, the range of values investigated for the dimensionless length scale parameter 0 ≤ l /a ≤ 0.002 is similar to that considered by dos Santos et al [41]. The critical dimensionless velocity increases with the normalized length scale, bringing out that size effects hinder the emergence of plastic shocks.…”
Section: Resultssupporting
confidence: 67%
“…The extension of the hypervelocity cavity expansion model of Cohen and Durban [9] to size-dependent materials developed by dos Santos et al [41] has been used to determine the effect of size, induced by plastic strain gradient, on the formation of plastic shocks in porous materials. In particular, we have shown that the critical cavity expansion velocity for which plastic shocks emerge increases with the length scale parameter that controls the effect of size, and decreases with the material porosity, with the influence of porosity decreasing as the effect of size increases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These models are attractive in that they often provide closed-form relationships between hardness (the load on the indenter measured in the experiment) and the plastic and elastic parameters of the material. The ECMs based on various material models are proposed [Durban and Masri, 2008;Gao et al, 2006;Gao, 2006a,b;dos Santos et al, 2021]. It is widely accepted that cone indentation models are also suitable for Vickers and Berkovich indenters if the cone half-angle is 70.3   .…”
mentioning
confidence: 99%